THE IMPORTANCE OF THE PRACTICE OF COMPETITIVE GAMES KID’S ATHLETICS IN PHYSICAL EDUCATION FOR COLLEGE STUDENTS (11-12 YEARS) USING THE COOPERATIVE LEARNING STRATEGY - Bensikaddour, Habib; Mokrani, Djamel; benklaouz, Touati Ahmed; Benzidane, Houcine; Sebbane, Mohammed (European Scientific Journal, ESJ, 2015)
Physical education teachers should purposefully accept the fact that they are the role models in developing individual and group characteristics. In addition, teachers should structure competitive activities to maximize the participation of all students. In this regard, teaching physical education is an exciting experience. It is important that we teach more than just knowledge, skills, and strategies like cooperative strategy and other. From this perspective, the teacher must model the desired outcome in the same way he demonstrates the critical elements of a kids' athletics. The aim of this experimental study is to determine the effect of the practice of the cooperation strategy with a new concept of Kids' Athletics; their contribution towards the improvement of teaching conditions in lessons of Physical Education and Sports in middle School; and the improvement of sports performance among students of the middle School in long jump (m), shot put (m), sprint 50 m (s), and endurance racing 1000 m (s). Thus, this study is one of the very best practices that promote a higher level of participation among all students in physical education. It is designed to give children the pleasure of playing athletics. It helps them to embark on sprinting, endurance running, jumping, and throwing. Two groups of girls (aged 11 ± 0.65 years) participated in this study. The students were divided into experimental and control group (n=24). The results according to the research variables is characterized by significant differences (*p≤0.05). Consequently, teacher’s use of the cooperative learning techniques in physical education will encourage a higher level of participation among many students in the activities of the kids' athletics. Therefore, this will improve the physical performance of students and their relationships better than the traditional teaching method using a command style (Mosston & Ashworth, 2002).